2015
DOI: 10.1111/arcm.12204
|View full text |Cite
|
Sign up to set email alerts
|

First Investigations of In Situ Electrical Properties of Limestone Blocks of Ancient Monuments

Abstract: In situ rapid electrostatic investigations on calcareous stones of monuments provide information that strongly correlates with the geological characteristics of the stone and proves to be efficient for provenance identification and successive restoration. With a portable device, it is now possible to scan several thousand blocks on a face of a monument in a few hours. The evolution of the religious building construction practices between the 13th and the 17th centuries is studied. From the petrophysics point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…(2)Field measurements: in experiments conducted on dry calcareous stones of historical buildings (Souffaché et al . ) using an electrostatic multipole configuration at 31.25 kHz, a greater variability is noted in permittivity than in conductivity (the ratios of the interquartile to the median being 1.26 and 0.70, respectively). Again, a greater variability in permittivity was observed at the site of Qalat al Bahrain.…”
Section: Soil Permittivity In the Vlf–lf Frequency Rangementioning
confidence: 98%
“…(2)Field measurements: in experiments conducted on dry calcareous stones of historical buildings (Souffaché et al . ) using an electrostatic multipole configuration at 31.25 kHz, a greater variability is noted in permittivity than in conductivity (the ratios of the interquartile to the median being 1.26 and 0.70, respectively). Again, a greater variability in permittivity was observed at the site of Qalat al Bahrain.…”
Section: Soil Permittivity In the Vlf–lf Frequency Rangementioning
confidence: 98%
“…These latter play an important role in the response to the application of an electric field due to their high specific surface with ionic double layer (Stern and diffuse layers) surrounding the clay particles (Leroy and Revil, 2009). The in situ measurements on ancient monuments (Souffaché et al ., 2016) using a decimetric sized instrument showed over two different depth of investigation (approximately 10 cm and 20 cm) significant variations of both the real and imaginary components of the effective permittivity over the whole volume of masonry stones belonging to the facings. It is worth noting that in the older monuments, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the perspective of civil engineering applications and for construction, sedimentary rocks deserve special attention because builders have to be able to evaluate the interest of their extraction in situ and then to monitor over time their alteration in place in constructions. Restorers and building archaeologists have to assess their present health (Rozenbaum et al ., 2007) and also intend to identify the choices that could have been those of the builders of ancient monuments (Souffaché et al ., 2016). Good knowledge of the physical properties of these natural sedimentary materials is essential to achieve correct interpretations of the geophysical or non‐destructive tests whatever investigation technique is used.…”
Section: Introductionmentioning
confidence: 99%
“…The research established by environmental science practitioners demonstrated the effect of temperatures in soil freezes and thaw states [12], deciding the seed harvesting dates [13], and moreover it influences infiltration [14], soil water systems [15]. In the past current trends, extensive use of machine learning techniques has been helping the meteorological and environmental sciences to set up widely optimized harvest systems harnessing artificial intelligence (AI) [16], [17], [26], [18]- [25].…”
Section: Introductionmentioning
confidence: 99%